Gen Z's Contribution to Protecting Nature in the Islamic Environment - Sheyla Putri Ramadhany; Muh. Habibulloh (Aslama: Journal of Islamic Studies, 2026)
This article analyzes the contribution of Generation Z (Gen Z) Muslims to environmental conservation, based on strong Islamic environmental ethics. Amid the global ecological crisis, this study aims to identify the synergy between the theological mandate (caliph, mizan, prohibition of israf) and the characteristics of Gen Z as digital natives. Using a qualitative literature study method, it was found that Gen Z's main contributions are manifested in two pillars: (1) Digitalization of ecological da'wah through social media, which transforms conservation messages (Hifẓ al-Bī'ah) into massive visual content. (2) Implementation of zero waste behavior as a manifestation of the principle of wasatiyyah (moderation) and resistance to israf. Gen Z acts as digital ecological khatib and agents of change who actualize their faith into concrete actions, while simultaneously fulfilling Hifẓ an-Nasl (preservation of offspring) within the framework of maqasid sharia. However, challenges such as a lack of practical knowledge and infrastructure require strengthening the contextual Islamic Religious Education curriculum and agent of change. In conclusion, Gen Z is the vanguard of Islamic ecology, whose potential must be maximized to ensure the sustainability of the earth.